2004
DOI: 10.1143/jjap.44.l54
|View full text |Cite
|
Sign up to set email alerts
|

Protein Cryocrystallography Using Laser-Processed Crystal

Abstract: Some new results on stress invariance in plane anisotropic elasticity are presented.We show that, for a uaction boundary value problem. the stress field in a plane anisotropic elastic body with discontjnuous moduli and a variety of interface conditions remains invariant with an appropriate constant shift in elastic compliances. The reduced dependence of stress on elastic constants is then discussed in light of this result. It is also shown that for the same class of interface wnditions, the effective complianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Upon considering lower X-ray energies for native SAD, X-ray absorption owing to crystal thickness is a major issue (Arndt, 1984;Wagner et al, 2016;Liebschner et al, 2016). This can be overcome with spherical laser-shaped crystals (Kitano et al, 2004;Watanabe, 2006;Basu, Olieric et al, 2019) or with micrometre-sized crystals, which are now routinely used in the field of structural biology. High-multiplicity data are challenging to obtain from micrometre-sized (<30 mm) single crystals, but it has been shown that accurate native SAD data can be gleaned from such crystals at the synchrotron using serial crystallography approaches (Huang et al, 2015(Huang et al, , 2016(Huang et al, , 2018Diederichs & Wang, 2017;Weinert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Upon considering lower X-ray energies for native SAD, X-ray absorption owing to crystal thickness is a major issue (Arndt, 1984;Wagner et al, 2016;Liebschner et al, 2016). This can be overcome with spherical laser-shaped crystals (Kitano et al, 2004;Watanabe, 2006;Basu, Olieric et al, 2019) or with micrometre-sized crystals, which are now routinely used in the field of structural biology. High-multiplicity data are challenging to obtain from micrometre-sized (<30 mm) single crystals, but it has been shown that accurate native SAD data can be gleaned from such crystals at the synchrotron using serial crystallography approaches (Huang et al, 2015(Huang et al, , 2016(Huang et al, , 2018Diederichs & Wang, 2017;Weinert et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The laser beam was focused on the surface of the crystal avoiding thus shockwave induced crack formation. In order to allow in-situ observation and manipulation of crystal cuts, we performed microdissection operations for all four proteins being utilized (standard and LB) initially in an open aqueous solution drop rather than in a flash-frozen cryoloop [22]. The freely floating protein crystals and the convective flow induced by evaporation did, however, not allow clear cuts.…”
Section: Laser-microdissectionmentioning
confidence: 99%
“…We are aware that the selection of mosaic blocks for X-ray nanodiffraction techniques would represent a methodological progress and could in particular improve the quality of structural refinements for high mosaicity crystals. For all of these reasons it is of interest exploring techniques allowing dissecting protein crystals, ultimately down to the level of individual mosaic blocks.In view of the generally fragile nature of biological matter, laser-optical techniques appear to be well suited for protein crystal manipulation [9,[14][15][16] and microdissection [17][18][19][20][21][22][23][24][25]. Our aim was exploring the ultimate size in coherently scattering crystal fragments obtainable by microdissection, principally for the model protein lysozyme.…”
mentioning
confidence: 99%
“…Lower energy X-ray is favorable to enhance the anomalous signals but on the other hand X-ray absorption by sample, solvent, and air hinders the diffraction data collection. Here, we present a method minimizing the X-ray absorption; the solvent portion of a mounted frozen crystal is removed or the mounted crystal is spherically shaped by the deep UV laser processing technique 1,2 . In this study, crystals of BphA4 and LigM proteins with various size and shape were used.…”
mentioning
confidence: 99%